Sparse Coding for Transform Domain-Based Sparse OFDM Channel Estimation - Nazzal, Mahmoud; Aygul, Mehmet Ali; Gorcin, Ali; Arslan, Huseyin (IEEE, 2019)
In orthogonal frequency division multiplexing (OFDM) systems, frequency domain pilot-aided channel estimation is based on interpolating a down-sampled version of the channel frequency response. This is achieved by transforming the channel frequency response to the time domain, eliminating time-domain channel coefficients beyond a given delay spread, and transforming back to the frequency domain. A sliding window is used to identify the most dominant channel coefficients within a prescribed delay spread which will be retained, where others will be eliminated. This setting relies on assuming a consecutive channel tap distribution and overlooks possible channel sparsity. To take advantage of this sparsity, we propose a method for obtaining the channel taps as a sparse recovery process. The proposed method is shown to substantially improve the channel estimation quality. The improvement is commensurate with the sparsity of the channel.
Keywords: Sparse coding; OFDM; channel estimation; Engineering; Telecommunications